DESAIN SPESIAL MAINTENANCE (PEMELIHARAAN KHUSUS) SALURAN DAERAH IRIGASI WAY RILAU LAMPUNG SELATAN - Besperi Besperi (Universitas Bengkulu, 2019)
The maintenance works of irrigation network are needed to maintain irrigation infrastructure to be well functioned and operable. The canals shall be defected due to natural causes which would make the dimension to become nonstandard, hence the effort to maintain the canals to be well functioned is needed to be conducted by the government by means of special maintenance. Maintenance shall be categorized into 4 types of activity, i.e. continuous maintenance, periodic maintenance, emergency maintenance and annual maintenance. Canals handlings shall not be conducted physically only hence the effort to increase the efficiency by means of operational and maintenance activity and by means of maintenance and upgrading of skill and knowledge of the farmers as water resource users shall be conducted following the physical maintenance, hence the farmers could solve their problem considering water usage management independently. The research was conducted by means of site research. It was expected that by the research, the effort to repair the defected or unserviceable canals as it was expected shall be conducted by the government and the water resource users.